An approach of controlling the inverter-based generator for use in an islanded microgrid - Suchart Janjornmanit; Sakorn Panta; Vishnu Thonglek (Institute of Advanced Engineering and Science, 2020)
The controls of power generation by the inverter-based generator are proposed in this work. The proposed control adjusts the active power output by varying the phase angle instead of the conventional frequency variation. The benefit of operating the network by a fixed frequency is that it eradicates the problems associated with the frequency deviation. The PID controls with recommended gain adjustment are proposed to control the power generation. The power generation schemes are adapted from the classical power generation by the synchronous generator, where the modes of operation are Swing, PV and PQ mode. The proposed three modes of operation are adequate to operate fully in a small-scale power system such as in an islanded microgrid. A case study of operating the proposed controls in a microgrid by simulation is used to demonstrate the feasibility of implementation of the controls.